PENDAMPINGAN KADER POSYANDU MELALUI PELATIHAN PEMANTAUAN STATUS KESEHATAN BALITA DAN KONSELING GIZI SEBAGAI UPAYA MENURUNKAN KEJADIAN STUNTING - Retna Puspitadewi, Teresia; Jannah, Roudlotul; Wahyurianto, Yasin (Jurnal Ilmiah Tatengkorang, 2024)
Stunting is a condition of failure to grow in toddlers due to chronic malnutrition for 1,000 HPK, The lack of exposure of mothers of toddlers and posyandu cadres about stunting is predicted to be the cause of the lack of social support, therefore it is necessary to educate the public about the health status of toddlers through screening. The purpose of community service activities is to provide assistance to Posyandu Cadres and mothers of toddlers on Monitoring the Nutritional Status of Toddlers and Nutrition Counseling as an effort to reduce the incidence of stunting in Tunah Village, Tuban Regency. The results of the first phase of activities on July 9, 2024 were counseling on stunting, nutrition for toddlers, and a demonstration of toddler menu processing by PERSAGI. From the results of this activity, it was obtained that there was a difference in knowledge with a significance of 0.000 with a p value of < 0.05, which means that there was an influence of the treatment or education provided on the improvement of participants' knowledge. Phase 2 on July 15, 2024, assisted the skills of posyandu cadres for anthropometric measurements obtained from 50 toddlers almost entirely (86%) with normal LILA, almost all (82%) LILA with normal toddlers, and most (54%) with BMI less than normal. The results of this measurement illustrate the condition of toddlers in Tunah village who have a malnourished status who are at risk of stunting. In the assistance of processing the toddler menu, 26 sample menus for toddlers were produced. This mentoring activity needs to be continued with the cooperation of the District, Puskesmas so that this community service activity is on target and successful as an effort to participate in the success of the government program to realize the acceleration of stunting reduction in toddlers Stunting merupakan kondisi gagal tumbuh pada balita akibat kekurangan gizi kronis selama 1.000 HPK, Kurang terpaparnya ibu balita dan kader posyandu tentang stunting diprediksi menjadi penyebab kurangnya dukungan sosial, oleh karenanya diperlukan edukasi pengetahuan dan pemahaman masyarakat tentang status kesehatan balita melalui skreening. Tujuan kegiatan pengabdian masyarakat memberikan Pendampingan pada Kader Posyandu dan ibu balita tentang Pemantauan Status Gizi Balita dan Konseling Gizi sebagai upaya menurunkan Kejadian Stunting di Desa Tunah Kabupaten Tuban. Hasil kegiatan tahap I tgl 9 Juli 2024 dilakukan penyuluhan tentang stunting, nutrisi balita, serta Demonstrasi pengolahan menu balita oleh PERSAGI. Dari hasil kegiatan ini didapatkan perbedaan pengetahuan dengan signifikansi 0,000 dengan p value < 0,05 diartikan ada pengaruh dari perlakuanatau edukasi yang diberikan pada peningkatan pengetahuan peserta. Tahap 2 tanggal 15 juli 2024 dilakukan pendampingan ketrampilan kader posyandu untuk pengukuran antropometri didapatkan dari 50 balita hampir seluruhnya (86%) LILA normal, LIKA hampir seluruhnya (82%) balita normal, dan IMT sebagian besar (54%) kurang dari normal. Hasil pengukuran ini menggambarkan kondisi balita didesa Tunah memiliki status gizi kurang yang berisiko mengalami stunting. Pada pendampingan pengolahan menu balita dihasilkan 26 contoh menu bagi balita. Kegiatan pendampingan ini perlu dilanjutkan dengan kerjasama pihak Kecamatan, Puskesmas agar kegiatan pengabdian masyarakat ini tepat sasaran dan berhasil guna sebagai upaya ikut serta mensukseskan program pemerintah mewujudkan percepatan penurunan Stunting pada balita